2013
DOI: 10.1021/es304346p
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the Uptake of Silver Nanoparticles and Ions to HepG2 Cells

Abstract: The toxic mechanism of silver nanoparticles (AgNPs) is still debating, partially because of the common co-occurrence and the lack of methods for separation of AgNPs and Ag(+) in biological matrices. For the first time, Triton-X 114-based cloud point extraction (CPE) was proposed to separate AgNPs and Ag(+) in the cell lysates of exposed HepG2 cells. Cell lysates were subjected to CPE after adding Na2S2O3, which facilitated the transfer of AgNPs into the nether Triton X-114-rich phase by salt effect and the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
85
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(89 citation statements)
references
References 37 publications
(79 reference statements)
3
85
1
Order By: Relevance
“…However, we circumvented this issue by looking at the portions of Ag ions and nAg particles inside the cells using the technique of cloud point extraction. 29 We followed this optimized method of cloud point extraction for separation of nAg particles and Ag ions in mammalian cells (a schematic diagram described in Figure 6A), as previously described. 29 We demonstrated that over 82.1% of Ag existed in the form of nanoparticles, with less than 17.9% as Ag ions inside MEL cells ( Figure 6B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, we circumvented this issue by looking at the portions of Ag ions and nAg particles inside the cells using the technique of cloud point extraction. 29 We followed this optimized method of cloud point extraction for separation of nAg particles and Ag ions in mammalian cells (a schematic diagram described in Figure 6A), as previously described. 29 We demonstrated that over 82.1% of Ag existed in the form of nanoparticles, with less than 17.9% as Ag ions inside MEL cells ( Figure 6B).…”
Section: Resultsmentioning
confidence: 99%
“…29 We followed this optimized method of cloud point extraction for separation of nAg particles and Ag ions in mammalian cells (a schematic diagram described in Figure 6A), as previously described. 29 We demonstrated that over 82.1% of Ag existed in the form of nanoparticles, with less than 17.9% as Ag ions inside MEL cells ( Figure 6B). Similar to our finding, Yu and colleagues documented that about 10.3% of Ag presented as ions in exposed Hep G2 cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The interference of Ag + was negligible when the concentration of Ag + was lower than two times that of AgNPs [5]. It was successfully applied to determine AgNPs and Ag + in environmental samples such as commercial available products [7], HepG2 cells [9] and municipal wastewater [10,11]. Previous study reported the speciation analysis of AgNPs and Ag + in six antibacterial products based on CPE [7].…”
Section: Cloud Point Extractionmentioning
confidence: 99%
“…As a result, nanoscale silver particles in the effluent was relatively low (< 12 ng/L), indicating that wastewater treatment plants were not the pollution source of nanoscale silver particles to the aquatic system. The CPE method allows us to quantify the uptake of AgNPs and Ag + to cells as well [9]. Under the optimized conditions, AgNPs and Ag + can be readily separated and quantified in HepG2 cells.…”
Section: Cloud Point Extractionmentioning
confidence: 99%